Penggunaan Strategi, Metode, dan Media Pembelajaran PKn SD Berbasis Belajar Aktif Melalui Kegiatan Bermain Peran - - Ruminiati (Sekolah Dasar : Kajian Teori dan Praktik Pendidikan, 2007)
Abstract: Strategy, method and medium of learning are an important component in an education world. There are 3 factors also take an important role in the students character development in the PKn elementary. The influence of globalization stream requires the education to form the student to have a high activity. Because of that, the children of elementary age should have high activity and have good behavior. To reach this demand, best the combination of strategy, method and medium an combination in PKn is the best instrument for of learning. Trough play a role model the students can have a high activity.